Designing and Developing Learning APPS for ESL Learners - Ismail Fayed; Azidah Abu Ziden (International Conference on Education and Language (ICEL), 2014)
In this paper, action research is used to investigate the possibility of integrating easily customized learning apps in teaching English language skills in the Foundation Program at Qatar University. A variety of approaches and processesfor developing and integrating simple web-based interactive apps for ESL learners will be presented. An understanding of how to develop and design asimplem-learning app will be discussed. A variety of review materials, interactive, communicative tools could be implemented at this session. Using augmented-reality and reusable learning objects in designing learning activities will also be introduced in this workshop.